“Ensayo comparativo de rendimiento de tres híbridos de tomate ( lycopersicon sculentum L. mill) en Lamas-región San Martín” - Hidalgo Vigil, Leonardo (2000)
Presently investigation work was studied the hybrid yield of three of tomato (Carmelo, Lerica, Alonso). compared with a witness (I Laugh Big Improved), to be the variety that more you sowing in the area of the Peruvian east and to demonstrate that looking for varieties and hybrid altemative we increase the production and productivity. The wmk was carried out in the District of you Lick 920 rn.s.n.rn. that it is in the area of Jjfo of Tropical dry Forest (bs-T) in the Forest of the Peru. Tbe objecfü.-es of the present work were to evaluate the adaptation and the hybrid new yield of three of tomato, for consumption in fresh or industrial use in relation to the variety local Irnproved Big River and to carry out the economic analysis by means of the relationship Cost-I Benefit and to determine theír profitability. The used design was the D esign Totally at random, with four treatments and four repetitions. They registered the following observations: germination Percentage (mastic), prendimiento percentage, day to the floración, number of flowers for inflorescence, days to the maturation of tbe fruit, total number of fruits for p1ant, commercia1 fruits, plant height, commercial yield, kilograms for plant, deshierbos number, total yield. The work settled June 27 1 996 and he/she ended in October of 1 996. The total area of the work was of 380 m2 , being the treatment T 0 (var. Jmproved Big river) of bigger yield of 58 600 Kg/ha, having a net profit of S /. 51 493,50 and the relationship Cost-I Benefit it was of 11,74%, but the treatment T 2 (Hybrid Lerica) it was the but economic since he/she obtained a net profit of S /. 50 158,30 and the relationsbip Cost-I Benefit it was of 11 ,47%.